2020
DOI: 10.12998/wjcc.v8.i15.3349
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography, magnetic resonance imaging, and F-deoxyglucose positron emission computed tomography/computed tomography findings of alveolar soft part sarcoma with calcification in the thigh: A case report

Abstract: BACKGROUND Alveolar soft part sarcoma (ASPS) is an extremely rare malignant sarcoma, accounting for less than 1% of all soft-tissue sarcomas. However, limited information is available on multimodal imaging [computed tomography (CT), magnetic resonance imaging (MRI), and positron emission computed tomography/computed tomography (PET/CT)] of ASPS. CASE SUMMARY This study reports a case of a 35-year-old female patient with ASPS of the left thigh with lung metastasis. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, there are no previous reports regarding FDG uptake in a case of orbital ASPS. The maximum FDG uptake of SUV in patients with ASPS in other body parts is 1.8 -10.1 [22][23][24][25] . A previous study reported the presence of thrombosed tumor vessels [3] .…”
Section: Discussionmentioning
confidence: 95%
“…To the best of our knowledge, there are no previous reports regarding FDG uptake in a case of orbital ASPS. The maximum FDG uptake of SUV in patients with ASPS in other body parts is 1.8 -10.1 [22][23][24][25] . A previous study reported the presence of thrombosed tumor vessels [3] .…”
Section: Discussionmentioning
confidence: 95%
“…Biological imaging is very important in the early identification of an unhealthy state, which has been widely used in biomedical diagnosis. The current biological imaging methods include fluorescence imaging, magnetic resonance imaging (MRI), computed tomography (CT), emission CT, photothermal imaging, Raman imaging, ultrasound imaging, and photoacoustic imaging . Fluorescence imaging has lower cost and higher sensitivity than other imaging tools, and the operation and its use are relatively simple and flexible; therefore, fluorescence biological imaging has been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Our case manifests as a soft tissue mass of the lower limb with intense FDG uptake on PET/CT mimicking malignancy. When soft tissue masses of the lower limbs are encountered, lymphoma, 5 epithelioid hemangioendothelioma, 6 alveolar soft part sarcoma, 7 undifferentiated pleomorphic sarcoma, 8 IgG4-related disease, 9 metastasis, 10,11 intramuscular myxoma, 12 and malignant peripheral nerve sheath tumor 13 should be considered in the differential diagnosis. Except for myxoma (mild FDG uptake), these lesions could have intense FDG uptake.…”
mentioning
confidence: 99%